Development of destination personality scale and factors influencing archaeological tourists' behavioural intentions in Malaysia - Pong, Kok Shiong (2022)
The development of archaeological tourism brings significant economics impact to a country’s growth domestic product and local community. This economic growth is beneficial to a country as a source of income. Nevertheless, the arrival of mass tourists to these sites might undoubtedly lead to negative consequences to some extent. The ability to strike a balance between tourism development and the efforts to preserve these archaeological sites are important for the long-term development of these sites. This task, however, is extremely difficult and should not be the sole responsibility of the site management and government. Tourists should also play an active role in the preservation effort. Therefore, this study is conducted to investigate behavioural intentions among archaeological tourists at the selected archaeological sites in Malaysia. The current study, guided by Personality Traits Theory, Stimulus Response Theory, and Stimulus Organism Responses (S-O-R) model, aims to develop, and validate the archaeological destination personality scale and to investigate the role of destination personality, interpretation, place attachment, authenticity, destination attractiveness, destination reputation as the stimulus and emotions as organism while tourists’ behavioural intentions as response at archaeological destination context. This study employs three studies by recruiting tourists (N= 1600) who have visited the archaeological sites in Malaysia, namely Bujang Valley (BV), Lenggong Valley World Heritage Site (LVWHS), and Niah National Park (NNP). Study 1 aims to generate and validate the destination personality items for archaeological sites. A total of 450 tourists were recruited at the three archaeological sites. Study 2 aims to purify the items and assess the stability of the scale’s factor structure. This study was able to recruit 750 respondents, and the data was used to investigate the archaeological destination personality dimensions and factor structure stability. Study 3 is conducted at archaeological sites to assess the predictive validation of archaeological destination personality among 400 respondents. The archaeological destination personality was found to be a multidimensional construct consisting of Masculine, Leadership-oriented, Legendary, Discoverable, and Wise. Furthermore, it was found that destination personality, interpretation, place attachment, authenticity, and destination attractiveness were positively influencing emotions. In addition, interpretation, authenticity, destination attractiveness and emotions were found to be significantly affecting intentions to recommend, while interpretation, place attachment, authenticity, and emotions were found to be significantly influencing the tourists’ intention to revisit, and lastly, intention to preserve was influenced by interpretation, place attachment, and emotions. Finally, emotions mediate the relationship between destination personality, interpretation, place attachment, authenticity, destination attractiveness, and behavioural intentions (i.e., intention to recommend, intention to revisit, and intention to preserve). The findings contribute to the existing literature by broadening the destination personality scale of archaeological destinations. Furthermore, by extending the stimulus organism response model, the current findings provide new insight to the existing literature. In practice, the findings of this study provide marketing strategies to archaeological site marketers for promotion and protection purposes. Destination marketers should use archaeological destination personality to build destination identity to attract tourists. Furthermore, interpretation and authenticity can be used to boost archaeological site promotion and preservation.